Dampak Orang Tua Pilih Kasih Terhadap Tekanan Emosional: Andil Relasi Saudara Kandung - Kristiana, Dessy; Sahrani, Riana (Universitas Muria Kudus, 2025)
Statistical data on mental health has been raising awareness of the need for attention to this issue. One of the factors that can affect a person's mental health is emotional distress, which can have various causes. The experience of individuals who receive different treatment from their parents (parental differential treatment) while growing up with their siblings can be a cause of emotional distress, even when the individual is already grown up. This study examined the role of Sibling Relationships as a moderator in the relationship between parental differential treatment and emotional distress in adults. Participants were 216 individuals aged 20 years and over, had siblings who lived and grew up together with the same parents before living independently. Using quantitative methods, with data collection employing non-probability sampling techniques using the Sibling Relationship Questionnaire (SRQ), Sibling Inventory of Differential Treatment (SIDE), and the Depression Anxiety Stress Scale. (DASS). The research findings indicate there is a role of Sibling Relationship as a moderator in the relationship between Parental Differential Treatment and Emotional Distress in adults. The implication is that Sibling Relationship can act as a factor that weakens or strengthens the impact of Parental Differential Treatment on the Emotional Distress in adulthood. Data statistik mengenai kesehatan mental telah menimbulkan kesadaran perlunya perhatian akan hal tersebut. Salah satu faktor yang dapat mempengaruhi kesehatan mental seseorang adalah tekanan emosional yang dialami, dengan penyebab beragam. Pengalaman individu yang mendapatkan perlakuan berbeda dari orang tua (parental differential treatment) semasa bertumbuh bersama saudara kandungnya dapat menjadi penyebab dari tekanan emosional (emotional distress), bahkan ketika individu yang bersangkutan sudah dewasa. Penelitian ini menguji peranan Relasi Saudara Kandung sebagai moderator dalam hubungan antara perlakuan berbeda dari orang tua dan tekanan emosional pada orang dewasa. Partisipan berjumlah 216 individu berusia 20 tahun ke atas, memiliki saudara kandung yang tinggal dan bertumbuh bersama dengan orang tua yang sama sebelum hidup mandiri. Metode yang digunakan pada penelitian ini adalah kuantitatif, pengambilan data menggunakan teknik pengambilan data non-probability sampling menggunakan alat ukur Sibling Relationship Questionnaire (SRQ), Sibling Inventory of Differential Treatment (SIDE), dan Depression Anxiety Stress Scale (DASS). Hasil penelitian menunjukkan adanya peran relasi saudara kandung sebagai moderator dalam hubungan antara perlakuan berbeda dari orang tua dan tekanan emosional pada orang dewasa. Implikasinya, relasi saudara kandung dapat berperan sebagai faktor yang memperlemah atau memperkuat dampak dari Perlakuan Berbeda dari Orang Tua terhadap Tekanan Emosional yang pada orang dewasa.